Teleost Metamorphosis: The Role of Thyroid Hormone - Campinho, Marco António (Frontiers in Endocrinology, 2019)
In most teleosts, metamorphosis encompasses a dramatic post-natal developmental process where the free-swimming larvae undergo a series of morphological, cellular and physiological changes that enable the larvae to become a fully formed, albeit sexually immature, juvenile fish. In all teleosts studied to date thyroid hormones (TH) drive metamorphosis, being the necessary and sufficient factors behind this developmental transition. During metamorphosis, negative regulation of thyrotropin by thyroxine (T4) is relaxed allowing higher whole-body levels of T4 that enable specific responses at the tissue/cellular level. Higher local thyroid cellular signalling leads to cell-specific responses that bring about localised developmental events. TH orchestrate in a spatial-temporal manner all local developmental changes so that in the end a fully functional organism arises. In bilateral teleost species, the most evident metamorphic morphological change underlies a transition to a more streamlined body. In the pleuronectiform lineage (flatfishes) these metamorphic morphological changes are more dramatic. The most evident is the migration of one eye to the opposite side of the head and the symmetric pelagic larva development into an asymmetric benthic juvenile. This transition encompasses a dramatic loss of the embryonic derived dorsal-ventral and left-right axis. The embryonic dorsal-ventral axis becomes the left-right axis whereas the embryonic left-right axis becomes, irrespectively, the dorsal-ventral axis of the juvenile animal. This event is an unparalleled morphological change in vertebrate development and a remarkable display of the capacity of TH-signalling in shaping adaptation and evolution in teleosts. Notwithstanding all this knowledge, there are still fundamental questions in teleost metamorphosis left unanswered: how is achieved the central regulation of metamorphosis and the neuroendocrine network involved is unclear; the detailed cellular and molecular events that give rise to the developmental processes occurring during teleost metamorphosis are still mostly unknown. Also in flatfish comparatively little is still known about the developmental processes behind asymmetric development. This review summarises the current knowledge on teleost metamorphosis and explores the gaps that still need to be challenged.